Caracterização de Bacteriófagos Infectando Isolados Clínicos de Pseudomonas aeruginosa Armazenados em uma Coleção de Cultura - Mingrone, Roberta Cristina Cabral [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
To isolate, to concentrate and to purify bacteriophages from isolates of P. aeruginosa; To observe the capacity of bacteriophages to infect isolates of P. aeruginosa susceptible and multiresitant to antimicrobial; To caractherize bacteriphages by electronic microscopy techniques. 10 isolates of Pseudomonas aeruginosa from LEMC culture collection were submitted to the experiments of ideal temperature for the lyse region appearance in the MaConkey culture plate and 2 extraction methods for the concentration of the phages, clorophorm (Silankorva) and filtration plus centrifugation (Bergan). Three infected clinical isolates of multiresistant P. aeruginosa an one susceptible isolate ( PA01) were evaluated by 3 transmission electron microscopy techniques to caractherize phages morphologically (“on grid”, “on drop” and direct extraction from the lyse region of the culture plate). The ideal temperature to obtain lyses region was 37°C. The stock solutions, obtained through the methodologies of Sillankorva and Bergan, had satisfactory results in infecting the multiresistant isolate and the negative control. Among the 3 techniques of electronic microscopy tested the direct from the lyse plate was the best to obtain the micrography of the phages

Isolar, concentrar e purificar bacteriófagos de amostras de P. aeruginosa; Observar a capacidade infectante dos bacteriófagos em amostras de P. aeruginosa sensíveis e multirresistentes à antimicrobianos; Caracterizar os bacteriófagos através de técnicas de microscopia eletrônica. Foram estudadas 10 amostras de Pseudomonas aeruginosa originárias da coleção de cultura do LEMC foram submetidas aos experimentos de teste de temperatura ideal para o aparecimento do halo de lise em placa de cultura MaConkey e a dois métodos de extração para concentração dos fagos em uma solução estoque com clorofórmio (Sillankorva) e com filtração e centrifugação (Bergan). Três amostras infectadas de P. aeruginosa multirresistentes de isolados clínicos e a amostra controle PA01, multissensível foram avaliadas por TRÊS técnicas de microscopia eletrônica de transmissão para caracterizar eventuais fagos morfologicamente (“on grid”, “on drop” e extração direta do halo de lise em placa de cultura). A temperatura de 37°C foi ideal para obtenção de halo de lise. As soluções estoque obtidas, através das metodologias de Sillankorva e Bergan, tiveram resultado satisfatório na infecção dos isolados clínicos multirresistentes e controle negativo para fago. Dentre as três técnicas testadas de microscopia eletrônica a direta da placa de lise foi a mais adequada para a obtenção de micrografia dos fagos
Keywords: Pseudomonas aeruginosa; Bacteriófagos; Biologia molecular; Microscopia eletronica